The role of Artificial Intelligence (AI) in cybersecurity: threats and defenses - Shamala, Palaniappan; Chinniah, Muruga (Universiti Teknologi MARA, Johor, 2025)
Artificial intelligence (AI) is changing cybersecurity by making both attack and defense tactics stronger. Cybercriminals take advantage of AI to come up with smarter threats. Industries are deploying AI-powered security tools to discover threats, prevent them, and respond to them. To protect systems and lower hacking risks, AI plays an important role. We could say it is now more important than ever to protect against these risks.